All about hip replacement - Trahair, Richard (Oxford University Press, 1998)
This book records the experiences of the author and thirteen other patients who have had the operation. They talk about their troubles with the old hips, reaching the difficult decision to have the operation, the strenuous process of finding appropriate surgeons and hospitals, and their preparations for the operation. Richard Trahair, an author and psychologist who has recently had hip replacement himself, weaves these people's hopes and concerns with professional advice from surgeons, rheumatologists, physiotherapists, nurses, and occupational therapists to provide a full, informed picture of the operation from several different viewpoints